INEFFECTIVENESS SENTENCE IN STUDENT’S THESIS OF PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA STKIP PGRI SUMATERA BARAT - Upit Yulianti; Rahayu Fitri; Febrina Riska Putri; Ayu Zalina Silvia (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is background by the frequent errors in writing effective sentences The formulation of the problem is how is the ineffectiveness of sentences in scientific papers of Indonesian Language and Literature Education Study Program students in STKIP PGRI West Sumatra. Research purpose to describe the ineffectiveness of sentences in scientific papers of Indonesian Language and Literature  Education Study Program students in STKIP PGRI West Sumatra. Research data is an ineffective sentence found in scientific papers (theses) students of the Indonesian Language and Literature Education Study Program STKIP PGRI West Sumatra. Data collection technique is the listening method.. Data analysis techniques are reading and marking, inventorying, classifying, analyzing and conducting discussions, discussions, conclusions of data and writing the results of research reports. The results of the study are sentence ineffectiveness based on the seven effective sentence requirements, namely the comparability of the structure, the parallelism of forms, the firmness of meaning, the effectiveness of words, the accuracy of reasoning, cohesion of ideas, and the logic of language.